2010
DOI: 10.1037/a0019049
|View full text |Cite
|
Sign up to set email alerts
|

Invariance detection within an interactive system: A perceptual gateway to language development.

Abstract: In this article, we hypothesize that invariance detection, a general perceptual phenomenon whereby organisms attend to relatively stable patterns or regularities, is an important means by which infants tune in to various aspects of spoken language. In so doing, we synthesize a substantial body of research on detection of regularities across the domains of speech perception, word segmentation, word-referent mapping, and grammar learning. In addition, we outline our framework for how invariance detection might s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
96
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(103 citation statements)
references
References 201 publications
(255 reference statements)
7
96
0
Order By: Relevance
“…We provide a bi-directional mechanistic explanation that involves the organism and its sociolinguistic environment - the ongoing interaction between infants’ perception and maternal scaffolding (Gogate & Hollich, 2010, 2013; Sullivan & Horrowitz, 1983; Yu, Ballard & Aslin, 2005). In general, caregivers coordinate their use of higher pitch, exaggerated intonation contours, elongated speech and longer pauses between utterances (Cooper, Abraham, Berman, & Statska, 1997; Fernald & Simon, 1984; Kitamura & Burnham, 2003) with simultaneous visual mouth movements (Bahrick & Pickens, 1988; Dodd, 1979; Legerstee, 1990; Meltzoff & Kuhl, 1994), more animated head movements and facial expressions (Smith & Strader, 2014; Walker-Andrews, 1997), and gestures using hands and body (Brand, Baldwin & Ashburn, 2002; Brand & Tapscott, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We provide a bi-directional mechanistic explanation that involves the organism and its sociolinguistic environment - the ongoing interaction between infants’ perception and maternal scaffolding (Gogate & Hollich, 2010, 2013; Sullivan & Horrowitz, 1983; Yu, Ballard & Aslin, 2005). In general, caregivers coordinate their use of higher pitch, exaggerated intonation contours, elongated speech and longer pauses between utterances (Cooper, Abraham, Berman, & Statska, 1997; Fernald & Simon, 1984; Kitamura & Burnham, 2003) with simultaneous visual mouth movements (Bahrick & Pickens, 1988; Dodd, 1979; Legerstee, 1990; Meltzoff & Kuhl, 1994), more animated head movements and facial expressions (Smith & Strader, 2014; Walker-Andrews, 1997), and gestures using hands and body (Brand, Baldwin & Ashburn, 2002; Brand & Tapscott, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In general, caregivers coordinate their use of higher pitch, exaggerated intonation contours, elongated speech and longer pauses between utterances (Cooper, Abraham, Berman, & Statska, 1997; Fernald & Simon, 1984; Kitamura & Burnham, 2003) with simultaneous visual mouth movements (Bahrick & Pickens, 1988; Dodd, 1979; Legerstee, 1990; Meltzoff & Kuhl, 1994), more animated head movements and facial expressions (Smith & Strader, 2014; Walker-Andrews, 1997), and gestures using hands and body (Brand, Baldwin & Ashburn, 2002; Brand & Tapscott, 2007). This coordinated information is amodal , invariant , and redundant; the same information conveyed to one sense modality is conveyed to another in the form of a common temporal structure, tempo, rhythm, and spatial colocation (see review by Gogate & Hollich, 2010). The intersensory redundancy is highly salient, elicits enhanced neural responses (Hyde, Jones, Flom, & Porter, 2011), and promotes infant perception, learning, and memory (Bahrick, 2010; Bahrick & Lickliter, 2002; 2012; Hollich, Newman, & Jusczyk, 2005; Lewkowicz, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that these features scaffold children's learning by providing an immediate and familiar structure for them to access their linguistic representation. They may then be able to analyse discrepancies between their own linguistic organisation and that of adults, and integrate new linguistic information into the language output and storage system (Nelson, 1989), as well as detect regularities for language mapping (Gogate and Hollich, 2010). These adult utterances may also be perceived by children as a form of pragmatically appropriate response and further motivate them to take the next turn and stay engaged in the conversation (Užgiris, Broome, and Kruper 1989;Pan, Sokolov, Rollins, and Snow 1991;Clark and Bernicot, 2008), further stimulating adults to match their input to the children's (Bohannon and Bonvillian, 2009) through a dynamic process that keeps the child within their zone of proximal development (Vygotsky, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…conventionally and contrastively) might reveal to the child the utility of adopting certain heuristics when they encounter further new words (e.g. Byers-Heinlein & Werker, 2009;Gogate & Hollich, 2010;Houston-Price, Caloghiris, & Raviglione, 2010;Callanan, this volume). What are children learning when learning a word?…”
Section: Current Debates and Future Researchmentioning
confidence: 99%